2012
DOI: 10.1242/jeb.068718
|View full text |Cite|
|
Sign up to set email alerts
|

A nicotinic acetylcholine receptor agonist affects honey bee sucrose responsiveness and decreases waggle dancing

Abstract: There was an error published in J. Exp. Biol. 215, 2022-2029 In the final sentence of paragraph 4 of 'Effects on SR' in the Results section, the total number of proboscis extensions is given, rather than percentages. The correct sentence is published below.On average, control nectar foragers had a lower mean total PER bee −1 (4.1±2.3 responses) than control pollen foragers (4.8±2.1 responses).The authors apologise for any confusion this may have caused. 2081

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 58 publications
6
103
0
Order By: Relevance
“…For example, 20 min [17] or 60 min [23] is sufficient for orally administered imidacloprid to elicit strong effects: reduction in foraging activity and longer foraging flights [17] and reduced waggle dancing [23]. Because we allowed our bees to unload their collected sucrose solution to nestmates, it is unclear how much imidacloprid they absorbed before exchanging their collected nectar with nestmates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 20 min [17] or 60 min [23] is sufficient for orally administered imidacloprid to elicit strong effects: reduction in foraging activity and longer foraging flights [17] and reduced waggle dancing [23]. Because we allowed our bees to unload their collected sucrose solution to nestmates, it is unclear how much imidacloprid they absorbed before exchanging their collected nectar with nestmates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sublethal doses of imidacloprid reduce olfactory [13], [20], [21] and visual [22] learning. Imidacloprid also evidently alters bee internal thresholds, elevating the sucrose response threshold and reducing waggle dancing even for very rich nectar sources [16], [23]. However, the role of imidacloprid in altering other types of decision-making remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Imidacloprid has been most widely studied, and its adverse effects on olfactory learning and memory have been well established (Decourtye et al 2004a, b; Williamson and Wright 2013) as well as visual learning (Han et al 2010). Imidacloprid affects gustatory sensitivity to sucrose, and also impairs the ability of honeybees to perform the waggle dance (Eiri and Nieh 2012; Lambin et al 2001), perhaps suggesting that they also impair motor function. One study, on the other hand, reported that sublethal doses of imidacloprid do not impair motor function of the proboscis extension response (Ramirez-Romero et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although spring mortality is characterized by a rapid disappearance of bee colonies (a typical short-term effect), scientific efforts were in most cases based on exposure to sublethal doses of neonicotinoids, which may weaken the colonies and make them more susceptible to both common and new diseases [10,[14][15][16][17][18][19]. In fact, since Greatti et al [20] demonstrated the possible release of seed coating insecticides through the fan drain of the pneumatic drilling machine during corn sowing and hypothesized that bees are exposed to the neonicotinoid-containing particles falling off to the vegetation at the field margin, experimental results have shown that the neonicotinoid content in nectar and pollen collected from the surrounding vegetation was always around 50 ppb or lower [12,[21][22][23], whereas higher doses are necessary for an acute toxic effect [13,[16][17][18]24].…”
Section: Introductionmentioning
confidence: 99%